Histopathological Characterization of Cases of Spontaneous Fatal Feline Severe Fever with Thrombocytopenia Syndrome, Japan - Sakai, Yusuke; Kuwabara, Yuko; Ishijima, Keita; Kagimoto, Saya; Mura, Serina; Tatemoto, Kango; Kuwata, Ryusei; Yonemitsu, Kenzo; Minami, Shohei; Kuroda, Yudai; Baba, Kenji; Okuda, Masaru; et al. (Emerging infectious diseases, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tickborne infectious disease caused by SFTS virus (SFTSV). We report 7 cases of spontaneous fatal SFTS in felines. Necropsies revealed characteristic lesions, including necrotizing lymphadenitis in 5 cases and necrotizing splenitis and SFTSV-positive blastic lymphocytes in all cases. We detected hemorrhagic lesions in the gastrointestinal tract in 6 cases and lungs in 3 cases, suggesting a more severe clinical course of SFTS in felids than in humans. We noted necrotic or ulcerative foci in the gastrointestinal tract in 3 cases, the lung in 2 cases, and the liver in 4 cases. We clarified that blastic lymphocytes are predominant targets of SFTSV and involved in induction of necrotic foci. We also found that thymic epithelial cells were additional targets of SFTSV. These results provide insights for diagnosing feline SFTS during pathological examination and demonstrate the similarity of feline and human SFTS cases.